2017
DOI: 10.5114/dr.2017.67383
|View full text |Cite
|
Sign up to set email alerts
|

Body image assessment and quality of life in patients with atopic dermatitis

Abstract: Introduction. Atopic dermatitis is a chronic and recurrent inflammatory skin condition. Significant skin lesions caused by the condition contribute to a negative perception of one's body. A negative body image may cause or enhance negative mental state, which, in a vicious circle, contributes to aggravation of the disease symptoms and deterioration of life quality. Especially skin lesions occurring on visible parts of the body may lead to a lack of acceptance by other people. Objective. To determine the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Many studies on NF1, ichthyosis, and birthmarks were able to show a link between the visibility or severity of the disorder, and a reduced QoL, depressive or anxious states, and an altered body image. These results echo other research conducted in subjects with chronic skin conditions such as atopic dermatitis [143][144][145], psoriasis [146][147][148][149][150][151] or vitiligo [152][153][154][155][156]. Other studies, conducted with "disfigured" patients, also resonate with our results [157]: we can mention craniofacial conditions, such as cleft lip or palate [158,159], or even people with burn injuries [160,161].…”
Section: Discussionsupporting
confidence: 89%
“…Many studies on NF1, ichthyosis, and birthmarks were able to show a link between the visibility or severity of the disorder, and a reduced QoL, depressive or anxious states, and an altered body image. These results echo other research conducted in subjects with chronic skin conditions such as atopic dermatitis [143][144][145], psoriasis [146][147][148][149][150][151] or vitiligo [152][153][154][155][156]. Other studies, conducted with "disfigured" patients, also resonate with our results [157]: we can mention craniofacial conditions, such as cleft lip or palate [158,159], or even people with burn injuries [160,161].…”
Section: Discussionsupporting
confidence: 89%
“…Nine studies explored relationships between patient‐assessed disease severity and DLQI scores and reported statistically significant medium‐ to large‐sized correlations whereby an increase in disease severity was associated with a decrease in QoL. Two studies explored gender differences and found a significant positive correlation between patient‐assessed disease severity and DLQI score ( P < 0.001) and between visible regions and DLQI score ( P = 0.001) for women, however neither of these correlations were observed in men.…”
Section: Resultsmentioning
confidence: 99%